A blended learning approach for teaching thoracic radiology to medical students: a proof-of-concept study - Stoehr, Fabian; Yang, Yang; Müller, Lukas; Gerstenmeier, Phyllis; Pinto dos Santos, Daniel; Dietz, Pavel; Weimer, Andreas; Ludwig, Michael; Kloeckner, Roman; Weimer, Johannes Matthias (Frontiers in Medicine, 2023)
Introduction The best way to impart knowledge to medical students is still unclear. Therefore, we designed a blended learning course in thoracic radiology including both “traditional” in-class time as well as online learning modules. The aims were (1) to investigate students’ attitudes toward this blended learning approach; and (2) to test whether it improved their knowledge about thoracic radiology. Methods A prospective study was conducted at the local medical center; 156 fourth-year medical students completed this study. Before and after the course, students had to complete (1) questionnaires to investigate their attitudes (7-point Likert scale); and (2) an objective test to assess their knowledge (multiple-choice/free text questions; results as % of correct answers). Results Regarding (1), the course led to an improvement in all items compared to baseline, exemplary: interest in thoracic radiology (precourse 4.2 vs. 5.4 postcourse) and the fulfillment of students’ expressed requirements regarding the teaching content (4.5 precourse vs. 6.2 postcourse). Furthermore, the great majority (88%) of our participants wished for more online learning offerings in the future. Regarding (2), the course led to improved knowledge on the objective test (precourse: 40% vs. postcourse: 63% correct answers). Conclusion This feasibility study showed the successful design and implementation of a blended learning approach in thoracic radiology. Furthermore, it revealed medical students’ positive attitudes toward this approach and showed an increased knowledge in thoracic radiology. Thus, such approaches might be used to enrich the teaching armamentarium in medical education and to further enhance interest and knowledge in thoracic diseases among medical students.